Electric shock–induced cataract - Ramatchandirane, Balamurugan; Ram, Shagila; Singh, Kiratmeet; SN Prasad, Shubhangi (Digital Journal of Ophthalmology, 2026)
A 44-year-old man presented at All India Institute of Medical Sciences, Mangalagiri, with a chief complaint of decreased vision in his left eye. Eight years earlier, he had experienced an electrical shock injury to his left hand from a home appliance, and since then he had been experiencing gradually decreasing vision in his left eye. He had no other systemic complaints. On examination, his best-corrected visual acuity was 6/6 (−1.50 DS) in the right eye and 6/18 (−1.75 DS) in the left eye. Intraocular pressure was normal in both eyes. Slit lamp examination revealed an anterior subcapsular cataract in the left eye, with a placoid appearance. This cataract, likely induced by the electric shock, had changed over the 8 years since the injury and appeared similar to anterior subcapsular cataract caused by blunt trauma. The posterior segment of both eyes appeared normal, and there were no abnormalities in the fellow eye. The patient underwent phacoemulsification cataract surgery with posterior chamber intraocular lens implantation, resulting in postoperative visual acuity of 6/6 in the left eye.